"ENHANCING PAEDIATRIC NURSING SKILLS THROUGH SIMULATION-LINKED PROBLEM-BASED LEARNING(S-PBL): A QUASI-EXPERIMENTAL STUDY" (CAHIERS MAGELLANES-NS, 2024)
Rapid advancement in health care area and the burden of disease get new challenges for health workers. The rapid spread of disease places a significant strain on the health care system and nursing schools and colleges, disrupting staffing and forcing students to complete their educational requirements in hospital. Due to student ‘s inability to put their theoretical knowledge in to practice. Both the theoretical and practical components in nursing education are divided in these circumstances.1S-PBL is a technique of problem-solving which makes use of real situations. In relation to Nursing education, it aids nurses in acquiring the problem-solving abilities required to address the numerous health issues come across during clinical practice. The ability to solve numerous patient health issues after graduation is an advantage for nursing students who have been taught clinical scenarios using simulation-linked problem-based learning but have not personally experienced them. Clinical simulation scenarios must reflect genuine clinical scenarios in order for the S-PBL to be effective2. Objectives: To compare pretest and post-test mean self-efficacy in paediatric nursing among nursing students exposed to Simulation linked Problem Based Learning (S-PBL) module. To compare mean post- test self- efficacy in paediatric nursing among nursing students exposed to Simulation linked Problem Based Learning (S-PBL) module and control group. To assess the association of self- efficacy in paediatric nursing among nursing students of Experimental and Control group with selected demographical variables. Material and methodsIn this study, A quantitative research methodology and a quasi-experimental (non- equivalent control group) research design was employed in the current investigation. 120 samples were used in the study, which used a purposive sampling strategy. There were 60 samples in the control group and 60 samples in the experimental group. Reliability of tool was done by Cronbach’s alpha on all the self- efficacy items to assess the instrument's dependability in its changed version utilizing the reliability of tool was 0.83. Result: Descriptive and inferential statistics were used to analyst the collected data. The findings of the study regarding comparison of pre -test mean self efficacy score in paediatric nursing among nursing students in experimental group at pre- test the mean self- efficacy score and SD was 43.9±10.83 and in control group the mean self -efficacy score and SD was 43.10±10.02. Independent t test was performed to compare their test self-efficacy score. The calculated t value and p value was 0.89 and 0.71 respectively. The t-test revealed that there was no significant difference between both the groups at pretest scores as p>0.05. The findings of the study about the comparison of level of self-efficacy score of nursing students in paediatric nursing before and after implementation of simulation linked problem- based learning module depict that the pre -test mean was 43.9 and SD ±10.83, whereas in post -test mean was 65.72 and SD ±9.34 the mean difference between pre -test and post- test self -efficacy score was very large i.e 21.82 and the difference is statistically significant. It was calculated by using student paired t test. The t value was 14.82, p=0.03. it shows significant at the level of p<0.05. Conclusion: It has been concluded that the simulation linked problem- based learning module is an effective and an innovative teaching pedagogy in improving the self- efficacy of B.Sc. Nursing 3rd year students in Paediatric Nursing practicum. The Post- test score comparison of level of self-efficacy score of nursing students in paediatric nursing in experimental and control group depict that in post- test mean was 65.72 and SD ±9.34 whereas in post- test of control group the mean of self- efficacy was 42.48 and SD was ±10.16 the mean difference between post- test self- efficacy score of both groups was very large i.e 23.24 and the difference is statistically significant. It was calculated by using independent t test. The t value was 15.32, p=0.02. it shows significant at the level of p<0.05.